2012
DOI: 10.5604/15093492.1012405
|View full text |Cite
|
Sign up to set email alerts
|

Wyniki leczenia dużych ubytków chrząstki stawu kolanowego za pomocą koncentratu komórek szpiku i membrany kolagenowej.

Abstract: 1. One-stage reconstruction of large cartilage lesions with bone marrow concentrate is an effective treatment modality. 2. Due to its lower cost it is a valuable alternative to autologous chondrocyte transplantation. 3. The study group requires 2-3 years of further monitoring to clinically verify this treatment modality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 9 publications
2
18
0
1
Order By: Relevance
“…Second-look arthroscopy revealed good defect filling with incorporation in the adjacent cartilage,203 and formation of a repair tissue of fibrocartilaginous209,210 or even hyaline-like nature 204. MRI evaluations also showed reconstruction of the cartilaginous surface and good integration of the repair tissue,206,207 while core biopsies yielded hyaline-like matrix or a mixture of hyaline and fibrocartilage 201. Finally, implantation of bone marrow-derived MSCs in an interconnected porous hydroxyapatite ceramic allowed for cartilage and bone regeneration in patients at second-look arthroscopy 199…”
Section: Applications For Articular Cartilage Defectsmentioning
confidence: 95%
See 1 more Smart Citation
“…Second-look arthroscopy revealed good defect filling with incorporation in the adjacent cartilage,203 and formation of a repair tissue of fibrocartilaginous209,210 or even hyaline-like nature 204. MRI evaluations also showed reconstruction of the cartilaginous surface and good integration of the repair tissue,206,207 while core biopsies yielded hyaline-like matrix or a mixture of hyaline and fibrocartilage 201. Finally, implantation of bone marrow-derived MSCs in an interconnected porous hydroxyapatite ceramic allowed for cartilage and bone regeneration in patients at second-look arthroscopy 199…”
Section: Applications For Articular Cartilage Defectsmentioning
confidence: 95%
“…Good subchondral and cartilage repair was also documented by scoring of cartilage repair using MRI evaluation 200. Alternatively, transplantation of isolated bone marrow-derived MSCs or marrow concentrates in collagen-derived elements (gel, scaffold, membrane, matrix) led to improved clinical outcomes in patients between 6 months and 5 years postoperatively using the KOOS functional and pain scale, visual analog scale, IKDC, and Lysholm score 203,206,207. Second-look arthroscopy revealed good defect filling with incorporation in the adjacent cartilage,203 and formation of a repair tissue of fibrocartilaginous209,210 or even hyaline-like nature 204.…”
Section: Applications For Articular Cartilage Defectsmentioning
confidence: 99%
“…Due to the diversity of terminology describing chondrectomy it was essential to begin by determining all terms used in the literature to describe the removal of pathologic joint cartilage, such as: chondrectomy, chondroplasty, excision cartilage, cartilage resection, cartilage remove, debride cartilage, chondral lesion excision, chondral debridement, chondral lesion debride, chondral lesion remove, curettage, remove chondral defect, or remove abnormal cartilage. Additionally, in order to narrow the search to knee joint cartilage surgeries, the following words were used as search terms: knee, cartilage, chondral lesion, microfracture, ACI (autologous chondrocyte implantation), AMIC (autologous matrix induced chondrogenesis), and MACI (matrix-induced autologous chon drocyte implantation) [7]. These criteria were met by 659 articles, which were subsequently were analyzed with regard to the content and description of surgical techniques.…”
Section: Methodsmentioning
confidence: 99%
“…Z uwa gi na ró żno rod ność ter mi no lo gii opi su ją cej proce du rę chon drek to mii, nie zbęd ne by ło na wstę pie ziden ty fi ko wa nie wszyst kich okre śleń sto so wa nych w li te ra tu rze, któ re opi su ją usu nię cie pa to lo gicz nej chrząst ki sta wo wej ta kich jak: chon drec to my, chondro pla sty, exci sion car ti la ge, car ti la ge re sec tion, carti la ge re mo ve, de bri de car ti la ge, chon dral le sion exci sion, chon dral de bri de ment, chon dral le sion debri de, chon dral le sion re mo ve, cur ret ta ge, re mo ve chon dral de fect, re mo ve ab nor mal car ti la ge. Do datko wo, ce lem za wę że nia wy szu ki wa nia do pro ce dur obej mu ją cych chrząst kę sta wu ko la no we go, uży to słów -knee, car ti la ge, chon dral le sion, mi kro frac ture, ACI (au to lo go us chon dro cy te im plan ta tion), AMIC (au to lo go us ma trix in du ced chon dro ge ne sis), MA CI (ma trix -in du ced au to lo go us chon dro cy te implan ta tion) [7]. Kry te ria speł nia ło 659 ar ty ku łów.…”
Section: Ma Te Riał I Me To Dyunclassified
“…These data suggest the one-step technique is a possible alternative for cartilage repair, obtaining improved functional scores and overcoming the disadvantages of previous techniques [ 45 ]. In this line, a recent case-series study reported treatment of large cartilage lesions of up to 12 cm 2 (ICRS grade III–IV) with BMC, resulting in significant improvement in all clinical scores for 52 out of 54 patients [ 46 ]. In a study comparing BMC, open autologous chondrocyte implantation (ACI), and ACI arthroscopy, clinical improvement was similar in all three groups [ 47 ] (Table 2 ).…”
Section: Introductionmentioning
confidence: 99%